Estudantes Macuxi e a educação profissional : percepções sobre o ensino no Campus Amajari - Dantas, Júlia Medeiros (2019)
This work was developed within an interpretative critical perspective in order to approach the Macuxi student's perception of his experiences as a student at the Amajari Campus of the Federal Institute of Roraima (IFRR) through the narratives of indigenous students, having as main objective to interpret the perceptions of these students about their experience of attending high school integrated with the technician at the IFRR Amajari Campus. We sought the theoretical support of Education Anthropology to understand the facts in the context of professional education. The methodology used is ethnographic in the perspective of Peirano (2014), when problematizing that ethnography is not a method. Therefore, this ethnography was fostered from the narratives of indigenous students of the Macuxi ethnic group Mutamba, Três Corações and Aningal, regularly enrolled in this institute, seeking to elucidate the anxieties and frustrations of indigenous youth attended by a professional technical school that could be captured, documenting what has been developed in terms of education with indigenous youth and propose a reflection on the actions that are being developed within a pedagogical proposal in the context of interculturality.